2016
DOI: 10.5603/fm.a2016.0021
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and morphometric features of mastoid emissary vein on multidetector computed tomography

Abstract: MEC and MF. (Folia Morphol 2016; 75, 4: 448-453)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Demirpolat et al 12 reported mean mastoid canal diameters of 1.58 AE 0.86 mm on the right and 1.48 AE 0.79 mm on the left. Mean MEC diameters in our study were 0.7 mm (IQR 0.5-1.0) in the control group and 1.6 mm (IQR 1.0-2.0) in the COM group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Demirpolat et al 12 reported mean mastoid canal diameters of 1.58 AE 0.86 mm on the right and 1.48 AE 0.79 mm on the left. Mean MEC diameters in our study were 0.7 mm (IQR 0.5-1.0) in the control group and 1.6 mm (IQR 1.0-2.0) in the COM group.…”
Section: Discussionmentioning
confidence: 99%
“…However, the emissary veins may represent a primary outflow route in patients with intracranial hypertension, high flow vascular malformation, obstruction in the internal jugular veins, or hypoplasia/aplasia. 3,12,13 The emissary veins prevent increases in intracranial pressure by providing cerebral venous drainage in patients with pathologies of the neck or base of the skull or with internal jugular vein occlusion. [15][16][17] Calibration of the emissary vein canals can increase under conditions of high vascular pressure or hypoplasia or aplasia of the jugular vein that may accompany states such as craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations